2018
DOI: 10.5194/tc-2018-6
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Satellite-derived sea-ice export and its impact on Arctic ice mass balance

Abstract: Abstract. Ice volume export drives variations of Arctic ice mass balance. It also represents a significant fresh water input to the North Atlantic, which could in turn modulate the intensity of the thermohaline circulation. We present the first estimates of winter sea ice volume export through the Fram Strait using CryoSat-2 sea ice thickness retrievals and three different drift products for the years 2010 to 2017. The export rates vary between -21 and -540 km 3 /month. We find that ice drift variability is th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…Consequently, the area export dominantly contributes more than the thinning of ice in controlling the Fram strait's ice volume export. These results are very well consistent with Ricker et al (2018) who, using different satellite products, observed and found the ice drift as the main driver of the annual and interannual ice volume export in Fram Strait.…”
Section: Trends Of Volume Exportsupporting
confidence: 92%
See 1 more Smart Citation
“…Consequently, the area export dominantly contributes more than the thinning of ice in controlling the Fram strait's ice volume export. These results are very well consistent with Ricker et al (2018) who, using different satellite products, observed and found the ice drift as the main driver of the annual and interannual ice volume export in Fram Strait.…”
Section: Trends Of Volume Exportsupporting
confidence: 92%
“…Smedsrud et al (2017) showed that sea ice export through Fram Strait preconditions early ice retreat and influences summer ice anomalies during some years which are higher after 2004. Following Ricker et al (2018), 54% of winter multiyear ice volume changes can be explained by the variations of ice volume export through the Fram Strait.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the impact of using the wind forcing from an anomalous year 30 (2009/10, stronger transpolar-drift), CICE-climforcing-wind20100ini, is stronger on April ice thickness (-0.13 m) than from the cold atmospheric conditions. This confirms the important role of sea ice dynamics and export through the Fram Strait in controlling the sea ice volume variability (Ricker et al, 2018).…”
Section: Impact Of Initial Conditions and Atmospheric Forcingsupporting
confidence: 67%
“…Following ERS, Giles et al [] used ESA Envisat (2002–2012) data from 2002–2008 to show a thinning of winter sea ice across the Arctic after the 2007 record minimum September sea ice extent that year. Subsequent studies have used CryoSat‐2 data to suggest that year‐to‐year fluctuations in winter Arctic sea ice thickness and volume since 2010 can be attributed to summer temperatures [Kwok & Cunningham, ; Tilling et al, ], wind‐driven ice convergence [Kwok & Cunningham, ], and ice export through the Fram Strait [Ricker et al, ]. To quantify long‐term trends in Arctic sea ice thickness and investigate the drivers of variability, it is necessary to combine multimission satellite data.…”
Section: Introductionmentioning
confidence: 99%